The Elderly in Brazil: reviewing public policies and training of health professionals - Gildo Volpato Gildo; Neiva Junkes Hoepers; Valdemira Santina Dagostin; Mágada Tessmann; Luciane Bisognin Ceretta (Jesuit University Ignatianum in Krakow, 2018)
RESEARCH OBJECTIVE: The objective of this study was to understand the elderly care policies approved in Brazil and to identify how the epidemiological profile of the population, especially the elderly is included in the curriculum and activities of the various undergraduate programs in the health area of UNESC. THE RESEARCH PROBLEM AND METHODS: The question is whether curricular guidelines and institutions address this need. It is a collective production, with a qualitative approach, based on a documentary analysis of the legislation and policies of the elderly in Brazil. Likewise, the documentary analysis of the Curriculum Guidelines of UNESC undergraduate programs was carried out as well as a survey of image records of activities carried out with seniors to illustrate some projects and actions developed. THE PROCESS OF ARGUMENTATION: The analysis related to the subject described is based, on the one hand, on the study of the literature related to the issues discussed (theoretical aspect of the publication) and, on the other hand, on the results of the analysis of public policies, curricular guidelines, course contents and the relevance of practical actions to the studied subject. RESEARCH RESULTS: The results of the research indicate that in the scope of the University the graduate courses in the health area began to rediscover the professional formation from the principles of SUS and the national and regional epidemiological aspects, including the needs of the elderly, mainly from the approval of the attention to the elderly. CONCLUSIONS, INNOVATIONS AND RECOMMENDATIONS: The university has to tease more and more on the subject with its teachers, giving those tools for teaching gerontology and geriatrics and the need for a qualified formation.